Impact of Changes in the Nomenclature of Rural Credit Banks on the Law on the Development and Strengthening of the Financial Sector - Kemalasari, Ni Putu Yuliana; Sara, Rineke (Greenation Publisher & Yayasan Global Resarch National, 2025)
The change in the nomenclature of Rural Credit Banks (BPR) to Rural Financing Banks in Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU P2SK) reflects a fundamental transformation in the direction of national financial sector policy. This change is not only symbolic but has a significant impact on the legal, institutional, and operational aspects of BPR. This study uses a normative legal method with a statutory and conceptual approach to analyze the legal implications, implementation challenges, and the need for new adaptive regulations. The analysis results show that the new nomenclature expands the role of BPRs in productive financing, opens up opportunities for integration with financial technology, and demands regulatory harmonization and strengthening the role of the OJK as a supervisory authority. The transformation is expected to enhance BPR's competitiveness in encouraging financial inclusion and people-based economic development.